1996
DOI: 10.2307/2945838
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Interethnic Cooperation

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
532
0
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 1,206 publications
(559 citation statements)
references
References 23 publications
19
532
0
8
Order By: Relevance
“…Support for the continental axis theory contributes to our nascent understanding of the roots of contemporary cultural diversity and its social implications. To be sure, we cannot claim from our study that historically conditioned cultural diversity, with the persistence of linguistic heterogeneity, consigns societies to low economic growth (9)(10)(11)(12), high rates of generalized distrust of others (7), high likelihood of local violence spiraling beyond original combatants (8), and failure by governments to provide public goods (5,6). Nonetheless, Diamond's continental axis theory reveals that these unfortunate outcomes are not a reflection of any particular culture's capacities, but rather the historical patterns fostered by geographical constraints that discouraged the integration of cultures.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Support for the continental axis theory contributes to our nascent understanding of the roots of contemporary cultural diversity and its social implications. To be sure, we cannot claim from our study that historically conditioned cultural diversity, with the persistence of linguistic heterogeneity, consigns societies to low economic growth (9)(10)(11)(12), high rates of generalized distrust of others (7), high likelihood of local violence spiraling beyond original combatants (8), and failure by governments to provide public goods (5,6). Nonetheless, Diamond's continental axis theory reveals that these unfortunate outcomes are not a reflection of any particular culture's capacities, but rather the historical patterns fostered by geographical constraints that discouraged the integration of cultures.…”
Section: Resultsmentioning
confidence: 87%
“…One implication of the theory, as we shall elaborate herein, is that east-west expansion of states delimits cultural diversity but north-south expansion sustains it. Research in the social sciences reveals that cultural diversity is associated with poorer provision of public goods (5,6), lower levels of interpersonal trust (7), higher probabilities of local violence (8), and lower rates of economic growth (9)(10)(11)(12). Indeed, if Diamond's axis theory holds, the identified historical patterns continue to impact society, economy, and polity.…”
mentioning
confidence: 99%
“…Of course, evidence exists which suggests that mutually exclusive ethnic and political identities and attitudes are capable of flux when the conditions or contexts In which intergroup relations are shaped are altered (Sonnenschein et al 2010;McGlynn et al 2004;Pickering 2006;Hewstone et al 2006). That sectarian hostilities persist does not necessarily imply that innovative forms of interethnic cooperation, and intra-ethnic heterogeneity, cannot take form (Fearon and Laitin 1996). Thus given that few survivors within societies emerging from conflict desire a return to the violence of the past, the provocative political strategies might be especially instrumental in explaining escalations of ethno-political hostilities during periods of "peace."…”
Section: Grounded Theory Analysis Of Interviews and Newspaper Reportsmentioning
confidence: 99%
“…They study the interaction between coalitions of di¤erent groups, whereas ethnicity increases the risk of con ‡ict by enforcing coalition membership. Fearon and Laitin (1996) emphasise intra-group enforcement of group members'cooperation with players from other ethnic groups. It is shown that policing inside a group can ensure peaceful relations outside the group.…”
Section: Ethnic Con ‡Ictmentioning
confidence: 99%